Drainage of Masseteric Abscess via Sublabial Approach: A Case Series (Bangladesh Journal of Medical Science, 2016)
Masseteric abscesses are usually drained through the external or trans-oral approach. Both choices have their own risks and benefits. We included in our case series 3 patients whom presented with painful facial swelling and were diagnosed as masseteric abscess. We performed the sublabial approach to drain the collection. Post-operatively, they recovered well and there were no recurrences. This technique and outcome of surgery are described.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.492-494